Protecting foreign investors in the smart energy grid sector and industry in Saudi Arabia: A comparative study under Vision 2030 - Tamam Abdul Latif Al-Jijkli (International Journal of Law Research and Studies, 2026)
This research aims to study the legal and regulatory framework for protecting foreign investors in the smart grid sector and industry in the Kingdom of Saudi Arabia, in light of the major economic transformations the Kingdom is undergoing as part of Vision 2030. Vision 2030 seeks to diversify energy sources and promote foreign investment in vital sectors, particularly renewable energy and related smart technologies. The importance of this research stems from the increasing reliance on smart grids as a component of modern energy infrastructure, given their operational efficiency and environmental sustainability. This makes them an attractive area for foreign investment and necessitates comprehensive legal protection to ensure the stability of these investments and enhance confidence in the Saudi investment environment. This research employs a comparative analytical approach, analyzing Saudi regulations related to investment and energy and comparing them with leading international models for protecting foreign investors in the energy sector. The aim is to determine the adequacy of national legislation in achieving a balance between investor protection and national sovereignty. The research concludes that Saudi Arabia has taken significant steps to enhance the protection of foreign investors by modernizing investment regulations, simplifying procedures, and providing legal guarantees. This contributes to improving the business environment and increasing foreign direct investment inflows. The research also revealed legal and regulatory challenges inherent to the smart grid sector, such as data protection, regulating public-private partnerships, and the need to develop more specialized legislative frameworks that keep pace with rapid technological advancements. The research concludes with a set of recommendations, most notably: developing legislation specific to smart grids, strengthening dispute resolution mechanisms, increasing transparency, and leveraging international best practices in this field. These measures will support the achievement of Vision 2030 goals and enhance the Kingdom’s position as an attractive investment hub in the advanced energy sector.